(untitled) (Research, Society and Development, 2020)
Objective: to know the access to primary care for adolescents hospitalized for conditions sensitive to primary health care. Methodology: This is a study with a qualitative approach, carried out in a public hospital of reference in the municipality of Santa Maria. The collection took place through semi-structured interviews in the second half of 2019. The data were submitted to thematic analysis. Results: For adolescents, access to primary care occurs when they are sick and when they need specific procedures such as vaccines and prescription of medications. Contact with health professionals occurs at school through health education activities. As for the adolescents’ expectations regarding health promotion, they reported that this practice is permeated by succinct statements, however, they envisage broader orientations. Conclusion: It is hoped that the research will make it possible to improve adolescent health care in the primary health care network by identifying the causes of hospitalization for conditions sensitive to primary care, reducing preventable diseases.